Establishment of a minor groove binder-probe based quantitative real time PCR to detect Borrelia burgdorferi sensu lato and differentiation of Borrelia spielmanii by ospA-specific conventional PCR - Strube, Christina (BioMed Central, 2010)
BACKGROUND: Borrelia burgdorferi sensu lato (sl), the causative agent of Lyme borreliosis, is transmitted by ticks of the genus Ixodes as vector. For identification of Borrelia infections in ticks a TaqMan™ minor groove binder (MGB) probe-based quantitative real time PCR (qPCR) was established targeting the 5S-23S intergenic spacer. Extension to a duplex qPCR included an Ixodes spp. positive control to verify successful DNA isolation. Besides qPCR, an ospA-specific conventional PCR for species-specific identification of B. spielmanii was established. Afterwards 1000 I. ricinus flagged in the city of Hanover, Germany, were investigated for B. burgdorferi sl infections followed by species identification. Furthermore, I. hexagonus ticks were investigated to proof applicability of the PCRs. RESULTS: Quantitative real time PCR (qPCR) identifying B. burgdorferi sl in ticks was able to detect 1-10 copies per reaction. B. spielmanii ospA-specific conventional PCR was also highly specific and showed no cross reactions with the other tested Borrelia species. From 1000 hanoveranian ticks 24.3% were positive compared to only 7.4% positives by dark-field microscopy. Related to tick stage 1.7% larvae, 18.1% nymphs, and 34.6% adults were positive. The most frequent species was B. garinii, followed by B. afzelii, B. spielmanii, B. valaisiana and B. burgdorferi sensu stricto (ss). 70.6% of I. ricinus were mono-infected, whereas 28.0% and 1.4% were infected with two and three Borrelia species, respectively. From 232 I. hexagonus collected from hedgehogs in different sites of Germany, qPCR detected 5.7% to be infected with B. burgdorferi sl, which were identified as B. afzelii, B. garinii and B. spielmanii. CONCLUSIONS: The evaluated qPCR to detect B. burgdorferi sl in Ixodes spp. is highly specific and sensitive. As a duplex qPCR including detection of Ixodes spp. DNA it is the first DNA based technique incorporating a control for successful DNA isolation from the vector tick. Establishment of a B. spielmanii specific conventional PCR filled the gap in PCR identification of principal European Borrelia genospecies. Practical application showed that all European pathogenic Borrelia spp. were present in I. ricinus flagged in recreational areas of the city of Hanover and confirmed I. hexagonus as reservoir for pathogenic Borrelia spp.